2012
DOI: 10.1016/j.molcel.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cells Have Constitutively Active Bax at the Golgi and Are Primed to Undergo Rapid Apoptosis

Abstract: Human embryonic stem (hES) cells activate a rapid apoptotic response after DNA damage but the underlying mechanisms are unknown. A critical mediator of apoptosis is Bax, which is reported to become active and translocate to the mitochondria only after apoptotic stimuli. Here we show that undifferentiated hES cells constitutively maintain Bax in its active conformation. Surprisingly, active Bax was maintained at the Golgi rather than at the mitochondria, thus allowing hES cells to effectively minimize the risks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
177
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(187 citation statements)
references
References 45 publications
9
177
1
Order By: Relevance
“…More importantly, several lines of evidence suggest that STAT1 signaling plays a pro-apoptotic role by upregulating the expression of caspases (43)(44)(45) or by repressing pro-survival NF-B signaling (46). Interestingly, hESCs are primed to undergo rapid apoptosis (47). It is thus possible that human pluripotent cells naturally suppress STAT1 phosphorylation to attenuate pro-apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, several lines of evidence suggest that STAT1 signaling plays a pro-apoptotic role by upregulating the expression of caspases (43)(44)(45) or by repressing pro-survival NF-B signaling (46). Interestingly, hESCs are primed to undergo rapid apoptosis (47). It is thus possible that human pluripotent cells naturally suppress STAT1 phosphorylation to attenuate pro-apoptotic signals.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, cellular responses to dsRNA and the subsequent response to type I IFNs would be disadvantageous to them. Last, human embryonic stem cells are primed to undergo rapid apoptosis (47). Because there is a well established association between STAT1 activation and apoptosis, it would make sense for human pluripotent cells to down-regulate STAT1 signaling by expressing a high level of SOCS1.…”
Section: Discussionmentioning
confidence: 99%
“…However, CGNPs responded to ABT 737 with extremely rapid induction of apoptosis, while we previously found that ABT 737 did not induce death in human ES cells (Dumitru et al, 2012). This differential sensitivity highlights key differences in the regulation of Bax in ES cells and CGNPs.…”
Section: Discussionmentioning
confidence: 76%
“…We have recently demonstrated that embryonic stem (ES) cells regulate apoptosis through a specialized mechanism in which proapoptotic Bax is constitutively activated and sequestered in the Golgi compartment (Dumitru et al, 2012). This mechanism eliminates stem cells with DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of Src and Ku70 in Suppression of ApoptosisPrevious studies reported that Ku70 plays a role in suppression of apoptosis (43)(44)(45)(46)(47)(48). To understand the regulation of the ability of Ku70 to suppress apoptosis, we attempted to establish stable Ku70-knockdown cell lines.…”
mentioning
confidence: 99%